Comparative Genomics Analysis Provides New Strategies for Bacteriostatic Ability of Bacillus velezensis HAB-2 - Xu, Peidong; Xie, Shangqian; Liu, Wenbo; Jin, Pengfei; Wei, Dandan; Yaseen, Dahar Ghulam; Wang, Yu; Miao, Weiguo (Frontiers in Microbiology, 2020)
Biocontrol formulations prepared from biocontrol bacteria are increasingly applied in sustainable agriculture. Notably, inoculants prepared from Bacillus strains have been proven efficient and environmentally friendly alternatives to chemical bactericides. The bacteria Bacillus velezensis HAB-2 (formerly classified as B. amyloliquefaciens HAB-2) is used as a biological control agent in agricultural fields. In this study, we reported a high-quality genome sequence of HAB-2 using third-generation sequencing technology (PacBio RS II). The 3.89 Mb genome encoded 3929 predicted genes. Comparative analysis among the genome sequences of reference strains B. velezensis FZB42, B. amyloliquefaciens DSM7 and B. subtilis 168 with the HAB-2 genome revealed obvious differences in the variable part of the genomes, while the core genome shared by FZB42 and HAB-2 was similar (96.14%). However, there were differences in the prophage region among the four strains. The numbers of prophage regions and coding genes in HAB-2 and FZB42 were smaller than for the other two strains. The HAB-2 genome showed superior ability to produce secondary metabolites and harbored13 gene clusters involved in synthesis of antifungal and antibacterial acting secondary metabolites. Furthermore, there were two unique clusters: one encoding lanthipeptide was involved in mersacidin synthesis and another encoding ladderane was shown to direct an unknown compound. Multidomain enzymes, such as nonribosomal peptide synthetase and polyketide synthase, control the biosynthesis of secondary metabolites and rely on 4′-phosphopantetheinyl transferases (PPTases). Key genes lpaH2 and acpS encoded PPTases in HAB-2 encoded 224 and 120 amino acids, respectively. The genomic comparison of revealed that HAB-2 possesses immense potential to synthesize antimicrobial acting secondary metabolites by regulating and controlling gene clusters. The prophage regions and genes encoding PPTases may provide novel insight for the bacteriostatic mechanism of Bacillus in the biological control of plant diseases.